SISTEM PENGENDALIAN KREDIT PADA BADAN USAHA MILIK DESA (BUMDES) SEMANGAT PEMUDA DESA GIRI SASAK - Lia Susanti; Animah Animah; Lalu Takdir Jumaidi (Jurnal Ilmiah Akuntansi Indonesia, 2022)
This study aims to reveal the internal control system for providing credit and handling bad credit problems at the Village-Owned Enterprises (BUMDes) Spirit of the Giri Sasak Village Youth. The research method used in this research is qualitative with a descriptive approach. This study uses data collection techniques in the form of: in-depth interviews, conservative observation, documentation and literature study. The results of this study indicate that the credit distribution control system and handling of bad credit problems BUMDes Spirit of Youth in Giri Sasak Village is still inadequate or there are still deficiencies seen from wrong credit analysis and bankruptcy, so that the effort taken is to continue to collect. This research still requires discipline from BUMDes employees in carrying out applicable credit policies or regulations as well as a firm attitude and further actions related to handling bad loans. This research assumes for credit management to improve the process of granting credit and handling problems related to bad loans in improving the internal control system that is more adequate for BUMDes.